ALASAN AUSTRALIA MENOLAK BANTUAN LUAR NEGERI SELANDIA BARU UNTUK MENAMPUNG PENGUNGSI DAN PENCARI SUAKA AUSTRALIA DI PAPUA NUGINI TAHUN 2016 - Aprilia, Ni Komang Anggreni; Darmiasih, D.A Wiwik; Sushanti, Sukma (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT This study aims to describe the reasons Australia refused New Zealand foreign aid to accommodate refugees and asylum seekers of Australia in Papua New Guinea 2016. The Australian government has refused an offer submitted by The New Zealand government to accommodate refugees and asylum seekers Australia in Papua New Guinea since 2013. Australia has also severely restricted refugees and asylum seekers to enter their country since 2013. Australia’s refusal is related to the government’s desire to protect its national security from illegal refugees and asylum seekers behind the Trans-Tasman Travel Arrangement (TTTA) relationship with New Zealand. This Research uses descriptive qualitative method with a framework of foreign policy related to foreign aid and national security in order to answer the formulation of the problem submitted. Keywords: Denial of Foreign Aid, Australian, Ilegal Refugees and Asylum Seekers, National Security, TTTA.